Fenomena "Mahram Haji" di Indonesia - Nurun Najwah (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2008)
The pilgrimage to Mecca is 5th of Islamic foundation for all the capable Moslem (istitha`ah) without consideration of the sex differences (male or female). It`s a duty of the women moslem are accompanied by mahram. In the one hand, this concept apparently protect safety of women. In the reality, in different contect, it represses opportunity of women to act of maximal devotion, included the pilgrimage to Mecca. So, this paper will describe reinterpretation of term of mahram from the text tradition of prophet Mohammed in Indonesian contect.